The Efficacy of Liposomal Bupivacaine in Managing Postoperative Pain, a Systematic Review and Meta-Analysis of Randomized Control Trials - Helena Soares Da Silva; Hualei Gong; Wenbo Wu; Zhenning Fang; Kai Mo (Riviera Publishing, 2025)
Postoperative pain, a significant surgical complication, presents a considerable challenge to the healthcare system, resulting in adverse outcomes, disability, prolonged hospitalization, and financial strain. This study seeks to evaluate the effectiveness of liposomal bupivacaine (LB) in postoperative pain management by a systematic review and meta-analysis of existing research. PubMed, CENTRAL, Embase, Web of Science, and Google Scholar were searched for randomized controlled trials (RCTs) published until January 2025, focusing on adults (18 years) undergoing surgical procedures where LB was administered via wound infiltration, nerve blocks, or periarticular injections. Primary outcomes included pain scores (VAS/NRS/BPI), opioid consumption, adverse events (e.g., nausea/vomiting), and patient satisfaction. A total of 763 papers were discovered in the literature, of which 21 (Barrington et al., 2017) were included. The pooled standardized mean difference (SMD) was -0.53, (95% CI, [-0.84, -0.23]; p = 0.0006) signifying a statistically significant decrease in pain levels favoring the intervention group. No significant disparity in opioid use was found between the two groups. The combined odds ratio (OR) was 0.78 (95% confidence interval (CI): [0.46 to 1.31]; [p = 0.35), indicating no significant difference in the incidence of nausea and vomiting. LB is effective in alleviating pain, diminishing opiate usage, and alleviating postoperative side effects.